2002
DOI: 10.1002/tox.10032
|View full text |Cite
|
Sign up to set email alerts
|

The fate of diesel hydrocarbons in soils and their effect on the germination of perennial ryegrass

Abstract: Hydrocarbon contamination in soils may be toxic to plants and soil microorganisms and act as a source of groundwater contamination. The objective of this study was to evaluate the fate of diesel in soils with or without added nutrients. The soils examined either had or had not a previous history of hydrocarbon contamination. Particular aspects examined were soil respiration, changes in microbial population, breakdown of diesel hydrocarbons, and phytotoxicity to the germination of perennial ryegrass. Soil respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
5
31
1
1
Order By: Relevance
“…The release of crude oil into the environment by oil spills is receiving worldwide attention (Millioli et al, 2009). The toxic effects of spent engine oil on germination of perennial rye grass, Amaranthus hybridus and maize growth performance was reported (Isirimah et al, 1989;Odjegba and Sadiq, 2002;Siddique and Adams, 2002). This study demonstrated that motor oil application at high concentration in soil has significant effect on the seedling growth performance of P. aculeata.…”
Section: Discussionsupporting
confidence: 58%
“…The release of crude oil into the environment by oil spills is receiving worldwide attention (Millioli et al, 2009). The toxic effects of spent engine oil on germination of perennial rye grass, Amaranthus hybridus and maize growth performance was reported (Isirimah et al, 1989;Odjegba and Sadiq, 2002;Siddique and Adams, 2002). This study demonstrated that motor oil application at high concentration in soil has significant effect on the seedling growth performance of P. aculeata.…”
Section: Discussionsupporting
confidence: 58%
“…During hydrocarbon exposures, acute toxicity is likely caused by lighter, more volatile hydrocarbons with a lower equivalent carbon number; heavy fractions with a high equivalent carbon number are more likely to cause chronic toxic effects [34][35][36][37]. Toxicity of petroleum hydrocarbons is strongly correlated with hydrocarbon fractions that have lower boiling points and octanol-water coefficients [log(K ow )], especially those within the nC10-nC19 range [12,[37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Soil and water remediation by non-biological technologies are expensive and incomplete (Medina-Bellver et al 2005;Siddiqui and Adams 2002). Moreover, bioremediation technology, the use of microorganisms to remove or detoxify contaminations, is a cost-effective and noninvasive method (Siddiqui and Adams 2002) and is highly efficient and can remove even trace levels of contaminants (Okoh 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bioremediation technology, the use of microorganisms to remove or detoxify contaminations, is a cost-effective and noninvasive method (Siddiqui and Adams 2002) and is highly efficient and can remove even trace levels of contaminants (Okoh 2006). However, it has been revealed that natural populations of microorganisms are able to remove environmental hydrocarbon pollutants including the products of petroleum industry, due to their diverse metabolic capabilities (Barin et al 2014).…”
Section: Introductionmentioning
confidence: 99%